Era uma vez um lugar... : um estudo da espacialidade na literatura infantojuvenil clássica e contemporânea - COSTA, Janete de Jesus Serra (2012)
The following research has as intent the investigation of the interdisciplinary links between the Children s and Young People s Literature and the Cultural Humanistic Geography, specifically in the Grimm Brothers fairy tales Little Red Riding Hood and Rapunzel, as well as in the Brazilian books for young people: The River and Me, of Lygia Bojunga Nunes and Ana Z., where are you going?, of Marina Colasanti, with the intention of focusing the theoretical affinities between Art and Science. Considering, by the light of the Cultural Humanistic Geography, the space as an essential category of this gender to the comprehension of the wonderful and fairy universe of these narratives, are broached the conceptions of space, place, landscape, lived world (Lebenswelt) and Being-in-the-World, to discover the complex relationship between literary art, imaginary, memory and symbolism, deeply associated to subjectivity, perception and experience of the places, in their positives and negatives aspects. Therefore, the analysis will emphasize the different ways of relationship with the lived world in the literary creation for children and young people, using the existentialist phenomenological methodology, as a type of theoretical comprehension that valorizes the human experience as an essential way to understand the personal involvement of man with the world and with the other men that lives in it. In this perspective, it is delimited how the topoanalysis, the topophilia and the topophobia are manifested in the classical and contemporary literary works, since the theoretical support that covers the multiplicity of the spatial representations.